Hak Politik Mantan Narapidana Untuk Mencalonkan Diri Sebagai Calon Kepala Daerah (Analisis terhadap Putusan MK. No. 42/PUU-XIII/2015) - Muhammad Lutfi Hardiyanto; Shalahudin Serba Bagus; Ahmad Munir (universitas islam darul ulum lamongan, 2017)
This article discusses the political rights of former inmates to run for candidates for a mayor. This article is the result of an analysis of the decision of the Constitutional Court. No. 42/PUU-XIII/2015 which gives political rights to former inmates to run for a mayor candidate. Basic consideration (ratio decidendi) of the decision of the Constitutional Court namely; the right to vote and to be elected by a person can only be withdrawn on the basis of a court decision not in accordance with the provisions of law; a person who has served the sentence and left the prison is essentially a person who has repented and regrets his actions, so it is not appropriate to be given further punishment through the provisions of the law which prohibite the candidacy in the election of regional head. On that basis, the Constitutional Court granted the right to former inmates to run for regional heads. The Constitutional Court ruling has a legal effect on former prisoners who were previously not allowed to run for regional head candidates. Following the verdict of the Constitutional Court the right of prisoners has the same right to run in elections.